KUALITAS PELAYANAN DAN PROMOSI TERHADAP MINAT BELI ULANG (STUDI PADA PELANGGAN BURGERKING PARAGON SEMARANG) - Nugroho Adhi Febriyanto; Widiartanto Widiartanto (Universitas Diponegoro, 2021)
Abstract: In modern times, the rapid advancement of technology, the presence of fast food in meeting human needs makes people indulge in fulfilling their daily food needs. Fast food restaurants are business companies engaged in services and provide services for providing food and beverages to customers. The fast food restaurant itself is one of the places to eat that is in great demand by consumers of all ages and from various circles. However, lately Burgerking Paragon Semarang has decreased due to a lack of interest in repurchasing. This is what makes Burgerking Paragon Semarang experience a decline. This type of research is explanatory research using questionnaires and google form as data collection methods. The purpose of this study was to determine the direct influence between service quality and promotion variables on repurchase interest. The research method used is Non-Probability Sampling technique with purposive sampling method. Data processing using SPSS 25.0. The samples collected were 100 respondents from Burgerking Paragon Semarang customers. Analysis of the data used is simple linear regression. The results of this study conclude that Service Quality and Promotion have a significant effect on Repurchase Interest at Burgerking Paragon SemarangKeywords: Kualitas Pelayanan, Promosi Minat Beli Ulang